Taxonomic characterization and ecological assessment of Philippine Palm Civet (Paradoxurus philippinensis) found in Caibiran, Biliran a preliminary study - Rosel, Vanessa Joy C.; Casas, Eulito Jr. V. (2017)
A preliminary study of a wild-caught civet from Barangay Union, Caibiran, Biliran aimed to give data on the morphology to characterize the taxonomy of the specimen; to provide information on the feeding behaviour and feeding ecology of the specimen in captivity; to generate initial data on the general behaviour of the species in captivity; and to describe the natural habitat of the specimen. The wild-caught civet was preliminary kept in a 1.5 x 1 x 1 m enclosure, branches of various heights and diameters were placed inside and a layer of dried leaves and grasses were also scattered on the floor. Morphological measurements of the specimen were recorded and it was identified as Paradoxurus philippinensis. Feeding behaviour and ecology were observed. The general behaviour of the specimen in captivity was observed directly defining six different behavioural states. Lastly, the natural habitat of the specimen was described. In captivity, Biliran civet uses locomotion the most (38.67%) and it rarely exhibit social behaviour (2%). Moreover, climbing and walking were used with almost the same frequency (38.59% and 35.02%, respectively) as its mode of locomotion. The civet prefers to eat mostly ripe bananas and fish in captivity. It was found inhabiting logged secondary forest significantly far from residential houses.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.